The Impact of Additives and Curing Conditions on the Mechanical Strength and Microstructural Development of MgO Based Systems - Taj, Khalilullah; Akturk, Busra; Ulukaya, Serhan (SPRINGER INTERNATIONAL PUBLISHING AG, 2023)
In this paper, the feasibility of utilization of reactive MgO (rMgO) cement as a single binder and its implementation in ternary mixes of nano-silica (NS), and pozzolans, i.e., ground granulated blast furnace slag (GGBFS), fly ash (FA), and micro-silica (MS) were investigated. In order to assess the workability and mechanical strength, flow diameter and compressive strength were measured. To evaluate the microstructural evolution, 28th day SEM analysis was conducted. In addition to air-curing, accelerated carbonation curing, which is imperative in crystallizing the binding phases in the MgO-based systems, was applied. The efficiency of carbonation curing was verified with pH evolution assessment. The impact of carbonation curing was evident from the increase in the 28(th)-day compressive strength of the control mix by 580%. The inclusion of FA and GGBFS was beneficial in terms of flowability. Through the SEM analysis, magnesium calcite is postulated to be the main binding phase, which most likely forms due to the presence of calcium sources in the raw materials. NS demonstrated a respectable increase, as much as 60%, in the compressive strength of all the mixes.
Keywords: reactive MgO; nano-silica; pozzolans; accelerated carbonation; microstructure; compressive strength; CEMENTS; Construction & Building Technology; Engineering; Materials Science